Development of Portable Gear Laser Measuring Devices - Qiu Zhou; Song Aiping; Pan Jianzhou; Huang Jiaming (Jixie chuandong)
Based on the linear laser displacement sensor, this research constructs a device which can measure the multiple deviations online of large gears. In this device, the tooth profile of the gear can be scanned by the linear laser displacement sensor, and the data of any tooth surface of the gear can be measured. The tooth profile curve of the gear can be fitted based on the least square method, and compared with the ideal model of the gear, the tooth profile and tooth distance deviation of the gear can be calculated by combining the radial polar coordinate angle comparison method. The measuring device proposed in this research is small in size, light in weight and easy to carry. The measuring method adopted is efficient and the gear deviation measured is accurate and reliable.